The Lower Triassic continental to transitional deposits of the Maritime Alps (NW Italy): stratigraphical and sedimentological features - Costamagna, Luca Giacomo (Journal of Mediterranean Earth Sciences, 2018)
The summarized results are here presented of an investigation undertaken on the continental to transitional siliciclastic Lower Triassic deposits of the Maritime Alps. Stratigraphic sections of the involved units has been described, analyzed and correlated A) to refer correctly the outcrops to the proper formational unit; B) to infer the stratigraphic relationships of the different lithofacies; C) to assess the depositional environments and their lateral variability through times, in order to relate them to the general transgressive trend of the Early Triassic.